Biochar additions can enhance soil structure and the physical stabilization of C in aggregates - Wang, Daoyuan; Fonte, Steven J.; Parikh, Sanjai J.; Six, Johan; Scow, Kate M. (Geoderma, 2017)
Biochar soil amendments are often considered as a soil carbon (C) sequestration strategy that can have beneficial impacts on a range of soil properties and plant production. We investigated the impact of two distinct types of biochar on soil chemical properties, microbial communities, soil aggregation and aggregate-associated C within two California agricultural soils in a laboratory incubation study (60weeks). Water stable aggregation and associated C were examined via wet-sieving to obtain four aggregate size classes: large macroaggregates (2000-8000μm), small macroaggregates (250-2000μm), microaggregates (53-250μm) and silt and clay fraction (<53μm). Biochars enhanced aggregation in the finer textured Yolo soil, with 217% and 126% average increases in mean weight diameter for a softwood biochar (pyrolyzed at 600-700°C with algal digestate) and a walnut shell biochar gasified at 900°C), respectively. The increase in aggregate stability was associated with an increase in physically-protected C incorporated into macroaggregates. Both biochars had substantial impacts on microbial community composition in both soils, but only increased microbial biomass in Yolo soil. In the coarser textured Vina soil, neither biochar had an effect on aggregation and the subsequent lack of soil organic matter (SOM) stabilization in macroaggregates was associated with a significant loss of soil C in both biochar treatments over the course of the incubation. Our results suggest that biochar can increase the physical-protection of SOM in Yolo soil by enhancing the proportion of C stored within macroaggregates and thus offers a novel mechanism by which biochar may contribute to soil C sequestration. Better understanding of these drivers and identifying soil conditions that determine whether biochar will physically protect SOM vs. stimulate soil C loss must be considered in managing agroecosystems for both mitigation of, and adaptation to, climate change. •Biochar can actively promote soil C storage by promoting aggregation and the physical stabilization of SOM.•Soil and biochar types greatly impacted soil chemical properties and microbial communities.•Biochar induced a greater loss of C in a soil where aggregation was not improved.